Hubungan antara Konsentrasi Cr(VI) dan Sifat Kimia Tanah: Informasi Awal untuk Remediasi Lahan Bekas Tambang di Kalimantan Selatan - Saidy, Akhmad Rizali; Badruzsaufari, Badruzsaufari (JOURNAL OF TROPICAL SOILS, 2009)
Relationship Between Concentration of Cr(VI) and Soil Chemical Characteristics: Preliminary Information for Remediation of Ex-mined Lands in the South Kalimantan (A.R. Saidy and Badruzsaufari): High concentration of heavy metals is frequently observed as an effect of mining activity. In order to determine relationship between concentration of Cr(VI) in ex-mined land and soil chemical characteristics, 15 of soils were sampled from ex-coal and chromate mined-lands in the South Kalimantan Province. Result of the experiment revealed that soils from the ex-mined lands contained 700 - 2645 mg Cr kg-1 soil. This research also showed that 0,73-1,35% of total Cr in these soils exist in the form of hexavalent chromium (Cr(VI)) that is toxic and carcinogen. Concentration of Cr(VI) in these soils were correlated significantly with soil pH in which increasing soil pH would lead to increase in concentration of Cr(VI). In addition, increasing in soil organic carbon will be followed by decreasing concentration of Cr(VI). Relationship between concentration of Cr(VI) and soil pH and organic carbon content could be useful for preliminary information for Cr reclamation of ex-mined lands.